Perception of corporate responsibility in the textile sector - EL-Sharnoubi, Ola (AUC Knowledge Fountain, 2015)
The purpose of the thesis is to investigate the potential of corporate responsibility (CR) in companies in the textile sector in Egypt and to explore the understanding of corporate responsibility amongst textile companies in Egypt, the perception of consumers and workers of CR and its benefits to the business, the employees, various stakeholders and the textile sector as a whole. This thesis researches the textile companies’ environmental, social and governance performance, sheds a light on the major challenges facing the industry and CR in the industry, as well as identifies potential opportunities for a sustainable sector development. The thesis discusses the relevance of CR to the industry and illustrates the limitations of CR in practice. It will give a background on CR, the different discourses of CR in the CSR literature. Additionally, the thesis investigates two main problematic questions: How does the ambiguity of defining CR serve its function? Is CR capable of resolving the conflict between corporate profit making and social expectations in the neoliberal order?